Usability evaluation of the digital archive of the Hellenic Broadcasting Corporation (ERT) - Garoufallou, Emmanouel; Mystakopoulos, Fotis; Siatri, Rania; Balatsoukas, Panos; Zafeiriou, Georgia (Qualitative and Quantitative Methods in Libraries; Vol 2 No 1 (2013): March 2013 Issue, 2017)
The Digital Archive of the Hellenic Broadcasting Corporation (ERT) is one of the most important attempts to preserve and disseminate the most valuable audio-visual archive of the Hellenic history and culture as seen and recorded throughout the years by the National Broadcasting Corporation. A usability survey was undertaken in order to evaluate the aforementioned digital archive using Jeng’s usability evaluation model. The model aims to evaluate Effectiveness, Efficiency Satisfaction and Learnability. The data collection instrument consisted of a questionnaire containing a series of scavenger hunt tasks, in conjunction with a series of evaluation questions. The study was carried out among undergraduate students of the Library Science and Information systems Department of the Technological Institute of Thessaloniki.